¿Cómo se tomó la decisión de suspender el culto en México en 1926? (Tzintzun, Revista de Estudios Históricos, 2016)
All historians agree that putting a halt to public worship by the Catholic Church was a decisive factor in the “cristero” uprising. How the Mexican bishopric made such an important decision and how the Vatican approved of it? The recent opening of all the archives in Rome and Mexico allows us to understand this confusing and mysterious episode. The division was very deep between the Mexican bishops and inside the Roman Curia, but a small and radical minority was able to convince the Pope that there was unanimity in favor of the suspension. Some Mexican Jesuits were able to win that battle both in Mexico and in Rome.
Keywords: Suspending worship; Jesuits; bishops; Curia; Pie XI